2014
DOI: 10.4103/2277-9175.146372
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between standard triple therapy and sequential therapy on eradication of Helicobacter pylori in uremic patients: A randomized clinical trial

Abstract: Background:The prevalence of peptic ulcer disease in hemodialysis dependent patients is higher than the general population. These patients are also more prone to upper gastrointestinal bleeding. The aim of this study was to compare the effects of a standard triple therapy with a sequential therapy on Helicobacter pylori eradication in azotemic and hemodialysis patients.Materials and Methods:Forty nine hemodialysis and azotemic patients, naïve to H. pylori treatment, were randomized into two groups to receive e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Several studies reported various eradication rates by triple therapy regimens ranging from 72.7% to 94.1% in hemodialysis-dependent patients [ 32 35 ]. In the clinical trial by Makhlough et al, the eradication rate of a standard triple therapy in CKD stage 3 was 50% (1/2), in CKD stage 4 was 75% (3/4), and in hemodialysis was 80% (12/15) [ 36 ]. In our study, which included larger case numbers than previous studies on CKD, the eradication rate in CKD stage 3 was 84.5% (82/97), in CKD stage 4 was 88.2% (15/17), and in hemodialysis was 87.5% (14/16).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported various eradication rates by triple therapy regimens ranging from 72.7% to 94.1% in hemodialysis-dependent patients [ 32 35 ]. In the clinical trial by Makhlough et al, the eradication rate of a standard triple therapy in CKD stage 3 was 50% (1/2), in CKD stage 4 was 75% (3/4), and in hemodialysis was 80% (12/15) [ 36 ]. In our study, which included larger case numbers than previous studies on CKD, the eradication rate in CKD stage 3 was 84.5% (82/97), in CKD stage 4 was 88.2% (15/17), and in hemodialysis was 87.5% (14/16).…”
Section: Discussionmentioning
confidence: 99%
“…H.pylori eradication rates were 76.2% and 87.5% by per-protocol analysis, respectively. 12 According to another study by Wang and co-workers on 40 hemodialysis patients, 7-day omeprazole-amoxicillin-clarithromycin(OAC) regimen could eradicate H.pylori in 86.8% of cases. 13 In addition, Tsukada and colleagues reported 82.1% eradication rate using the same regimen for 39 hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%